Orientasi Petani Bertani di Lahan Kering Kasus di Desa Jingkang Kecamatan Tanjung Medar Kabupaten Sumedang - Yayat Sukayat; Dika Supyandi; Gunardi Judawinata; Iwan Setiawan (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2019)
In the monetary crisis that occurred in 1998, the agricultural sector has shown its resilience as a hero in saving the nation's economic downturn. In the use of land for farming, no longer only pay attention to wetlands but begin to look at dry land, with all its characteristics such as tofografi (landscapes), water availability, and soil fertility, such as herbs and or medicines. The purpose of this study is to describe the business orientation ( cultural values) in farming. The research design is quantitative, with descriptive survey techniques from a sample size of 30 farmers. The results of the study, farmers' orientation in farming began to shift from social orientation to economic orientation, by keeping or aligning themselves with nature.